Systematic review on the approach to visible thinking in arts education - Landa Maymó, Marina; Monreal Guerrero, Inés María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The aim of this article is to carry out a systematic review in order to inform the scientific community about the state of the art of the implementation of the visible thinking approach in art schools. If the pedagogy of the instrument uses such an approach to achieve students’ comprehension skills, the study shows that there is a limited number of specific scientific publications dealing with this object of study and that, therefore, there is a wide field of research on this topic necessary to achieve an improvement in the effective learning of the instrument.